2011
DOI: 10.1590/s1678-91992011000300017
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa infarct following Viper bite: a paradox

Abstract: Cerebral infarction after a viper bite is relatively uncommon. A combination of factors has been implicated in the pathophysiology of infarct following snakebite. In this case report, the clinical outcome after a posterior circulation infarct and various possibilities that could lead to such a catastrophic event are discussed. The present study stresses the need to keep hydration, blood pressure and central venous pressure optimal in all snakebite patients. Cerebral infarction should be considered a differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In one case the patient survived but had no improvement in neurological status and was given poor prognosis 5. In the other case the patient recovered significantly 3.…”
Section: Discussionmentioning
confidence: 94%
“…In one case the patient survived but had no improvement in neurological status and was given poor prognosis 5. In the other case the patient recovered significantly 3.…”
Section: Discussionmentioning
confidence: 94%
“…Previous case reports have discussed similar cases where the patient died despite normal coagulation parameters. 10,14 Patient A also had paraplegia that could be explained as an MRI of the spine could not be done. Singh et al 15 have In our series, two patients presented with seizures despite having only posterior fossa infarcts (B, E).…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to earlier case reports. [10][11][12][13][14] The clinical outcome is better in patients with supratentorial infarcts following snake bite than posterior fossa infarcts. [5][6][7][8][9] This may be due to the rapid rise of intracranial pressure associated with posterior fossa infarcts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike cobra bite, neurological sequelae are extremely rare in viper bite. However, cases of cerebrovascular accident (cerebral infarction or cerebral haemorrhage) were reported by some studies [1][2][3] and neuromuscular weakness were observed [4]. Endocrine and metabolic complications after viper bite has been reported by several researchers [5].…”
Section: Introductionmentioning
confidence: 99%